Cancers due to infection and selected environmental factors: estimation of the attributable cancer burden in Germany - Gredner, Thomas; Behrens, Gundula; Stock, Christian; Brenner, Hermann; Mons, Ute (Deutsches Ärzteblatt, 2018)
BACKGROUND: Causal relationships with the occurrence of cancer have been established for a number of infections and environmental risk factors. - METHODS: Numbers and proportions (population-attributable fractions, PAF) of cancer cases attributable to these factors in Germany were calculated by sex and age groups for ages 35 to 84 years based on population projections, national cancer incidence, exposure data, and published risk estimates. - RESULTS: For 2018, more than 17 600 cancer cases (4.0% of all incident cancers) were estimated to be attributable to infections. The largest contributions come from Helicobacter pylori (n = 8764) and human papillomavirus (n = 7669) infections. Infection with hepatitis B and C, human immunodeficiency virus, and human herpesvirus 8 were estimated to cause 983 cases, 144 cases, and 116 cases, respectively. More than 5400 cancer cases (1.2% of all incident cancers) were estimated to be attributable to selected environmental factors, of which the largest contributor is indoor radon (n = 3185), followed by particulate matter (n = 1049), sunbed use (n = 892), and secondhand smoke (n = 309). - CONCLUSION: Of all cancers expected in 2018 in Germany, at least 5% are attributable to potentially avoidable infections and environmental factors. Further research should be directed towards more comprehensive identification and quantification of environmental risks as a basis for targeted cancer prevention.